To trust a Colton cowboy - Nussio, Dana (Coltons of Colorado., 2022)
"The threatening texts Kayla St. James is receiving insist she knows where something is hidden. Terrified, she confides in her boss, rancher Jasper Colton. Though Jasper's father sent her dad to prison, Kayla's only option is to trust him. But as the terror campaign intensifies, Kayla begins to care for Jasper despite her misgivings. Can two former enemies unite to take down a vicious stalker?" --